Persistent High Percentage of HLA-DR+CD38high CD8+ T Cells Associated With Immune Disorder and Disease Severity of COVID-19 - Du, Juan; Wei, Lirong; Li, Guoli; Hua, Mingxi; Sun, Yao; Wang, Di; Han, Kai; Yan, Yonghong; Song, Chuan; Song, Rui; Zhang, Henghui; Han, Junyan; et al. (Frontiers in Immunology, 2021)
Background: The global outbreak of coronavirus disease 2019 (COVID-19) has turned into a worldwide public health crisis and caused more than 100,000,000 severe cases. Progressive lymphopenia, especially in T cells, was a prominent clinical feature of severe COVID-19. Activated HLA-DR+CD38+CD8+T cells were enriched over a prolonged period from the lymphopenia patients who died from Ebola and influenza infection, and in severe patients infected with SARS-CoV-2. However, the CD38+HLA-DR+CD8+T population was reported to play contradictory roles in SARS-CoV-2 infection. Methods: A total of 42 COVID-19 patients, including 32 mild or moderate and 10 severe or critical cases, who received care at Beijing Ditan Hospital were recruited into this retrospective study. Blood samples were first collected within three days of the hospital admission and once every 3-7 days during hospitalization. The longitudinal flow cytometric data were examined during hospitalization. Moreover, we evaluated serum levels of 45 cytokines/chemokines/growth factors and 14 soluble checkpoints using Luminex multiplex assay longitudinally. Results: We revealed that the HLA-DR+CD38+CD8+T population was heterogeneous, and could be divided into two subsets with distinct characteristics: HLA-DR+CD38dim and HLA-DR+CD38hi. We observed a persistent accumulation of HLA-DR+CD38hiCD8+T cells in severe COVID-19 patients. These HLA-DR+CD38hiCD8+T cells were in a state of over-activation and consequent dysregulation manifested by expression of multiple inhibitory and stimulatory checkpoints, higher apoptotic sensitivity, impaired killing potential, and more exhausted transcriptional regulation compared to HLA-DR+CD38dimCD8+T cells. Moreover, the clinical and laboratory data supported that only HLA-DR+CD38hiCD8+T cells were associated with systemic inflammation, tissue injury, and immune disorders of severe COVID-19 patients. Conclusions: Our findings indicated that HLA-DR+CD38hiCD8+T cells were correlated with disease severity of COVID-19 rather than HLA-DR+CD38dim population.